Analisis Dimensi Profil Pelajar Pancasila Dalam Cerita Rakyat "Tupai dan Delak" - Aprima Tirsa; Mastiah Mastiah (Bestari: Jurnal Pendidikan dan Kebudayaan, 2023)
Abstract: This research aims to describe the dimensions of the profile of Pancasila students in the folk tale "Tupai and Delak". The method used in this research was descriptive method. The data source in this research is the folktale text "Tupai and Delak" told by the informant. Data collection techniques in this research were recording techniques, text observation, and interview techniques. The research instruments used in this research were the researcher as the key instrument, recording equipment, interview guide, and data cards. Data analysis using content analysis. The results of this research are that there are three dimensions of the Pancasila student profile, namely 1) the dimension of faith, devotion to God Almighty and noble character (morals towards humans), 2) the dimension of global diversity, and 3) the creative dimension.Keywords: Pancasila student profile dimensions, folklore, tupai and Delak. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan dimensi profil pelajar pancasila dalam cerita rakyat “Tupai dan Delak”. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. Sumber data dalam penelitian ini adalah teks cerita rakyat “Tupai dan Delak” yang dituturkan informan. Teknik pengumpulan data dalam penelitian ini adalah teknik perekaman, observasi teks, dan teknik wawancara. Instrumen penelitian yang digunakan dalam penelitian ini adalah peneliti sebagai instrumen kunci, alat perekam, pedoman wawancara, dan kartu data. Analisis data menggunakan konten analisis. Hasil penelitian ini adalah terdapat tiga dimensi profil pelajar pancasila, yaitu 1) Dimensi beriman, bertakwa kapada Tuhan Yang Maha Esa dan Berahlak Mulia (Akhlak kepada Manusia), 2) Dimensi kebhinekaan global, dan 3) Dimensi kreatif. Kata Kunci: Dimensi profil pelajar pancasila, cerita rakyat, Tupai dan Delak.